2004
DOI: 10.4049/jimmunol.172.11.7053
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Mitogen-Activated Protein Kinase Kinase Inhibitor U0126 in an Asthma Mouse Model

Abstract: Mitogen-activated protein kinase (MAPK) signaling cascade plays a pivotal role in the activation of inflammatory cells. Recent findings revealed that the activity of p42/44 MAPK (also known as extracellular signal-regulated kinase (ERK)) in the lungs was significantly higher in asthmatic mice than in normal controls. We hypothesized that inhibition of ERK activity may have anti-inflammatory effects in allergic asthma. BALB/c mice were sensitized with OVA and, upon OVA aerosol challenge, developed airway eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
207
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(216 citation statements)
references
References 48 publications
8
207
0
1
Order By: Relevance
“…Numerous reports have indicated a role of MAPK, particularly ERK1/2 and p38, in the regulation of COX-2 expression in monocytes [6], neuroblastoma cells [12] and epithelial cells [7], by LPS, IL-1b and TNF-a, respectively. On the other hand, an association between MAPK activity and allergic inflammation has been found previously in the lungs of asthmatic mice [9] or in the bronchoalveolar lavage fluids from asthmatic patients [8]. In agreement with these results, our work shows that the exposure of PBL from patients allergic to specific allergens promoted p38 and ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous reports have indicated a role of MAPK, particularly ERK1/2 and p38, in the regulation of COX-2 expression in monocytes [6], neuroblastoma cells [12] and epithelial cells [7], by LPS, IL-1b and TNF-a, respectively. On the other hand, an association between MAPK activity and allergic inflammation has been found previously in the lungs of asthmatic mice [9] or in the bronchoalveolar lavage fluids from asthmatic patients [8]. In agreement with these results, our work shows that the exposure of PBL from patients allergic to specific allergens promoted p38 and ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have pointed out a connection between this induction and the activation of MAPK-dependent pathways [6,7]. MAPK activities have also been associated with allergic inflammation [8,9]. The transcriptional activation of COX-2 is mediated by the binding of transcription factors to regulatory elements in the COX-2 promoter, such as nuclear factor of activated T cells (NF-AT) [10,11] or NF-jB [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the regulation of neoplastic cell proliferation, ERK has also been implicated in the control of signaling cascades associated with eosinophilia in asthma. Duan et al (48) reported that an MEK inhibitor dramatically inhibited OVAinduced lung tissue eosinophilia and airway hyperresponsiveness. Also, p38…”
Section: Discussionmentioning
confidence: 99%
“…To determine the extent of mucus production, goblet cell hyperplasia in the airway epithelium was quantified with a five-point grading system. 15,16) The adopted grading system was as follows: 0, no goblet cells; 1, Ͻ25%; 2, 25-50%; 3, 50-75%, and 4, Ͼ75%. The blinded quantitative analysis was performed with the described method previously.…”
Section: )mentioning
confidence: 99%